Epidemiology of paediatric trauma presenting to US emergency departments: 2006–2012. Issue 2 (22nd October 2017) - Avraham, Jacob B; Bhandari, Misha; Frangos, Spiros G; Levine, Deborah A; Tunik, Michael G; DiMaggio, Charles J
Abstract : Background: Traumatic injury is the leading cause of paediatric morbidity and mortality in the USA. We present updated national data on emergency department (ED) discharges for traumatic injury for a recent 7-year period. Methods: We conducted a descriptive epidemiological analysis of the Nationwide Emergency Department Sample Survey, the largest and most comprehensive database in the USA, for 2006–2012. Among children and adolescents, we tracked changes in injury mechanism and severity, cost of care, injury intent and the role of trauma centres. Results: There was an 8.3% (95% CI 7.7 to 8.9) decrease in the annual number of ED visits for traumatic injury in children and adolescents over the study period, from 8 557 904 (SE=5861) in 2006 to 7 846 912 (SE=5191) in 2012. The case-fatality rate was 0.04% for all injuries and 3.2% for severely injured children. Children and adolescents with high-mortality injury mechanisms were more than three times more likely to be treated at a level 1 trauma centre (OR=3.5, 95% CI 3.3 to 3.7), but were more no more likely to die (OR=0.96, 95% CI 0.93 to 1.00). Traumatic brain injury diagnoses increased 22.2% (95% CI 20.6 to 23.9) during the study period. Intentional assault accounted for 3% (SE=0.1) of all child and adolescent ED injury discharges and 7.2% (SE=0.3) of discharges among 15–19 year-olds. There was an 11.3% (95% CI 10.0 to 12.6) decline in motor vehicle injuries from 2009 to 2012. The total cost of care was $23 billion (SE=0.01), a 78% increase from 2006 to 2012. Conclusions: This analysis presents a recent portrait of paediatric trauma across the USA. These analyses indicate the important role and value of trauma centre care for injured children and adolescents, and that the most common causes and mechanisms of injury are preventable.